Usefulness of Neutrophil-to-Lymphocyte Ratio in Risk Stratification of Patients With Advanced Heart Failure - Benítes-Zapata, Vicente A. (2015)
Elevated neutrophil-to-lymphocyte ratio (NLR) has been associated with increased mortality in patients with acute heart failure (HF) and neoplastic diseases. We investigated the association between NLR and mortality or cardiac transplantation in a retrospective cohort of 527 patients presented to the Cleveland Clinic for evaluation of advanced HF therapy options from 2007 to 2010. Patients were divided according to low, intermediate, and high tertiles of NLR and were followed longitudinally for time to all-cause mortality or heart transplantation (primary outcome). The median NLR was 3.9 (interquartile range 2.5 to 6.5). In univariate analysis, intermediate and highest tertiles of NLR had a higher risk than the lowest tertile for the primary outcome and all-causes mortality. Compared with the lowest tertile, there was no difference in the risk of heart transplantation for intermediate and high tertiles. In multivariate analysis, compared with the lowest tertile, the intermediate and high NLR tertiles remained significantly associated with the primary outcome (hazard ratio [HR] [ 1.61, 95% confidence interval [CI] 1.10 to 2.37 and HR [ 1.55, 95% CI 1.02 to 2.36, respectively) and all-cause mortality (HR [ 1.83, 95% CI 1.07 to 3.14 and HR [ 2.16, 95% CI 1.21 to 3.83, respectively). In conclusion, elevated NLR is associated with increased mortality or heart transplantation risk in patients with advanced HF.